Perbandingan Pemilihan Antara Tipe Wellhead Conventional Dengan Wellhead Unihead - Nugroho Marsiyanto; Aly Rasyid; Sigit Widianto (Jurnal Bhara Petro Energi, 2022)
The wellhead is a surface well control device made of steel which forms a seal / baffle system to withstand bursts or leaks of liquid from the well to the surface composed of casing head (casing hanger) and tubing head (tubing hanger). Wellhead used in an oil or gas well must have a long runlife  because  an oil or  gas  well can  last up  to  decades,  and  if  it  is  necessary  to  replace  the wellhead  will  take  large  costs.  This  paper  determines  the  process  in  selecting  the  use  and effectiveness of wellhead and comparing conventional wellhead versus unihead wellhead at W well  that  is  efficient  and  safe  during  drilling  well  and  optimal  utilization  during  production process. Wellhead type selection process cover determining temperature class, material class, pressure  rating,  installation  costs,  and  in  terms  of  safety.  Based  on  the  selection  process,  W wellhead well has the temperature class used is class U, the material class used is the type FF- 0.5  or  HH-0.5,  for  a  pressure  rating  of  3000 psi,  and  in  terms  of  cost  it  is  more  economical to use unihead wellhead type.